How do Agency Problems Affect the Implied Cost of Capital? - Wu, Ching-Chih; Lin, Bing-Huei; Yang, Tung-Hsiao (Journal of Reviews on Global Economics, 2016)
We test the relationship between the implied cost of capital and two agency problems, free cash flows and overinvestment. We show that free cash flows have a significant negative impact on the implied cost of capital, but overinvestment has a significantly positive impact. In addition, the pay-for-performance sensitivity has a negative effect but the sensitivity of volatility has a significantly positive effect on the implied cost of capital. After taking the incentives into account, we find that the significance of the impact from both agency problems still exists. Finally, we conclude that well-designed executive compensation should focus on reducing overinvestment and the sensitivity of volatility.